Does occupational licensing impact incomes? A replication study for the German crafts case - Kaja von der Leyen (Journal for Labour Market Research, 2020)
Large variation in the estimated income premium of occupational licensing can be found in the existing literature. I revisit the natural experimental design of a change in the German crafts regulation in 2004, which removed the traditional licensing requirement for self-employment in certain trades, using official survey data and difference-in-differences estimation. Previous studies of this deregulation have found significant, yet small effects on the incomes of employees in deregulated trades. I focus on the incomes of the self-employed and find no robust effects. Multiple channels through which occupational licensing may affect incomes such as price and quality competition in the regulated market and possible competitive pressure from outsiders are identified, which may also explain why the effects of occupational licensing on incomes appear to be context-specific.
Keywords: I28; I39; J24; L51; 330; Labor markets; Occupational licensing; Monopoly rent; Natural experiment; Craftsmanship